The Crimean Khanate in 1736 according to the Account of the French Consul, Adam Yavorka - Avakov P.A.; Bespyatykh Yu.N. (Золотоордынское обозрение, 2020)
Research objective: An introduction to the scholarly circulation of a unique document of 1736 and the evaluation of its informative potential as a source on the history of the Crimean Khanate. Along the way, the authors reconstruct the circumstances of the creation of the document and the factors that determined its semantic focus and content. Research materials: An archived original of the document, first translated from German and accompanied by external and internal criticism on a wide range of contemporary sources and more recent studies. Results and novelty of the research: The account of the French consul, A. Yavorka, was recorded in the camp of the Russian army in the Crimea on the order of Field Marshal, Count B.Ch. Münnich. Thematically it is divided into three sections: an autobiographical story, intelligence information, and general geographic information. Being a clerical document, this source also fits into the wide context of foreign narratives about the Crimean Khanate. The account by A. Yavorka contains new information about his biography, the reaction of the Crimean elite to the invasion by the Russian army, the position of the Christian subjects of the Khan in wartime, the representatives of the Giray’s family, and the economy of the Crimean Khanate. Verification of the data in comparison with evidence from other sources suggests a high degree of reliability regarding the document under study. At the same time, the information of A. Yavorka about the structure of the nobility of the Crimean Khanate is not quite accurate, which is explained by the rather superficial acquaintance of the diplomat with this segment of public life in his host country.